Injection of mice with antibody to mouse interferon alpha/beta decreases the level of 2'-5' oligoadenylate synthetase in peritoneal macrophages. - Gresser, I (1985)
Injection of conventional or axenic weanling mice with potent sheep or goat antibody to mouse interferon alpha/beta resulted in a decrease in the basal level of 2-5A synthetase in resting peritoneal macrophages and rendered these cells permissive for vesicular stomatitis virus. There was a good inverse correlation between the level of 2-5A synthetase in peritoneal macrophages and the permissivity of these cells for vesicular stomatitis virus. The peritoneal macrophages of 1- and 2-week-old mice had low levels of 2-5A synthetase and were permissive for vesicular stomatitis virus, whereas at 3 weeks (and after) there was a marked increase in the level of 2-5A synthetase in peritoneal macrophages, and these cells were no longer permissive for vesicular stomatitis virus. We suggest that low levels of interferon alpha or beta or both are produced in normal mice, and that this interferon contributes to host defense by inducing and maintaining an antiviral state in some cells.